Cannabinoid Receptors CB1 and CB2 Modulate the Electroretinographic Waves in Vervet Monkeys. (16th March 2016) - Bouskila, Joseph; Harrar, Vanessa; Javadi, Pasha; Beierschmitt, Amy; Palmour, Roberta; Casanova, Christian; Bouchard, Jean-François; Ptito, Maurice
Abstract : The expression patterns of the cannabinoid receptor type 1 (CB1R) and the cannabinoid receptor type 2 (CB2R) are well documented in rodents and primates. In vervet monkeys, CB1R is present in the retinal neurons (photoreceptors, horizontal cells, bipolar cells, amacrine cells, and ganglion cells) and CB2R is exclusively found in the retinal glia (Müller cells). However, the role of these cannabinoid receptors in normal primate retinal function remains elusive. Using full-field electroretinography in adult vervet monkeys, we recorded changes in neural activity following the blockade of CB1R and CB2R by the intravitreal administration of their antagonists (AM251 and AM630, resp.) in photopic and scotopic conditions. Our results show that AM251 increases the photopic a-wave amplitude at high flash intensities, whereas AM630 increases the amplitude of both the photopic a- and b-waves. In scotopic conditions, both blockers increased the b-wave amplitude but did not change the a-wave amplitude. These findings suggest an important role of CB1R and CB2R in primate retinal function.